Host specificity of sheep and cattle nematodes in São Paulo state, Brazil - Amarante, AFT; Bagnola, J.; Amarante, MRV; Barbosa, M. A. (Elsevier B.V., 1997)
The trial was carried out to investigate parasite host specificity and to analyse the dynamics of infection with nematodes parasitizing sheep and catt:le raised together or separately in São Paulo state, Brazil, and, also to clarify doubts about the systematics of species of the genus Haemonchus on the basis of cytological and morphological studies. Ten steers and 32 ewes were randomly assigned to three paddocks (P), as follows: P1, 5 steers; P2, 5 steers and 16 ewes; and P3, 16 ewes. The animals remained on these paddocks in continuous grazing throughout the trial (1-yr period). Faecal exams and larvae counting on pasture were performed fortnightly. Once a month two tracer lambs were placed in each paddock, while two tracer calves were also placed, but only in the eighth month of the trial. All these animals were slaughtered for worm identification and counting. At the end of the trial, one steer and one ewe from P2, which showed high faecal egg counts, were also slaughtered for the same purpose. Nematodes identified cytogenetically as H. placei presented spicule hooks longer than those identified as H. contortus. The following distribution of parasites in cattle and sheep was observed: Bunostomum phlebotomum, H. similis, Mammomonogamus laryngeus strongly adapted to cattle, H. placei and Cooperia punctata more adapted to cattle than to sheep, Trichostrongylus axel and C. spatulata apparently more adapted to cattle, T. colubriformis strongly adapted to sheep, H. contortus more adapted to sheep than to cattle and C. curticei apparently more adapted to sheep. Cross-infection was shown to occur involving some species, however, with time the animals apparently eliminate the species that are not well adapted to them. Therefore, grazing management systems using cattle and sheep appear to be promising for worm control in southeastern Brazil. (C) 1997 Elsevier B.V. B.V.
Keywords: Haemonchus; Trichostrongylus; Cooperia; Mammomonogamus; cattle; nematoda; sheep; host specificity